A densely packed Sb2O3 nanosheet–graphene aerogel toward advanced sodium-ion batteries. Issue 19 (2nd May 2018) - Zhou, Jing; Yan, Bingyi; Yang, Jie; Yang, Yun; Zhou, Wei; Lan, Hao; Wang, Hua; Guo, Lin
Abstract : A densely packed Sb2 O3 nanosheets–graphene aerogel has been successfully synthesized by a facile amorphous-to-crystalline strategy. The as-prepared unique structure provides a robust support and stable buffer layer to maintain the structural stability during the electrochemical process, leading to superior sodium-ions storage performance. Abstract : As a promising anodic material for rechargeable batteries, Sb2 O3 has drawn increasing attention due to its high theoretical capacity and abundant natural deposits. However, poor cyclability and rate performance of Sb2 O3 derived from a large volume change during insertion/desertion reactions as well as a sluggish kinetic process restrict its practical application. Herein, we report a facile amorphous-to-crystalline strategy to synthesize a densely packed Sb2 O3 nanosheet–graphene aerogel as a novel anode for sodium ion batteries (SIBs). This Sb2 O3 /graphene composite displays a reversible capacity as high as 657.9 mA h g −1 even after 100 cycles at 0.1 A g −1, along with an excellent rate capacity of 356.8 mA h g −1 at 5.0 A g −1 . The superior electrochemical performance is attributed to the synergistic effects of densely packed Sb2 O3 nanosheets and graphene aerogel, which serves as both a robust support and stable buffer layer to maintain the structural stability of the nanocomposite, and enhances the electrode kinetics of electrolyte diffusion and electron transfer simultaneously. Hence, this densely-packed two-dimensional Sb2 O3 nanosheet–graphene aerogel can be a promising anode material for rechargeable SIBs due to its facile synthesis process and outstanding electrochemical performance.